Wybrane aspekty modlitwy chrześcijańskiej w dziełach Matta el-Maskine (1919–2006) - Adam Rybicki (Studia Koszalińsko-Kołobrzeskie)
The article presents selected aspects of the concept of prayer according to the contemporary Coptic monk Matt el-Maskine (1919–2006). The nature of prayer and its role in shaping the Christian attitude is the first part of the article. The second part is devoted to the fruits of prayer. The last part is an indication that Matta el-Maskine connected the topic of prayer with ecumenical efforts and saw their interconnection. The deep understanding of prayer contained in Matt el-Maskine’s works and at the same time showing it in many social contexts makes us consider this author a contemporary master of Christian spirituality who perfectly combines experience with knowledge, the tradition of the East with the tradition of the West, as well as theology with everyday life.